Impact of neoadjuvant chemotherapy on nodal regression and survival in oesophageal adenocarcinoma. Issue 5 (May 2022) - Evans, Richard PT.; Kamarajah, Sivesh K.; Kunene, Victoria; Zardo, Davide; Elshafie, Mona; Griffiths, Ewen A.
Abstract: Background: The prognostic value of lymph node regression (LNR) following neoadjuvant chemotherapy (nCT) for oesophageal and gastro-oeosphageal adenocarcinoma remains unclear. This study aimed to characterise the long-term survival outcomes of LNR in patients having resectional surgery after nCT. Methods: This study included patients undergoing oesophagectomy or extended total gastrectomy for oesophageal and junctional tumours (Siewert types 1, 2, 3) at the Queen Elizabeth Hospital Birmingham from 2012 to 2018. Lymph nodes retrieved at surgery were examined for evidence of a response to chemotherapy. Patients were classified as lymph node-negative (either negative nodes with no evidence of previous tumour involvement or negative with evidence of complete regression) or positive with either partial or no response. Results: This study identified 183 patients who received nCT, of which 71% (130/183) had positive lymph nodes. Of these 130 patients, 44% (57/130) had a lymph node response and 56% (73/130) did not. The remaining 53 patients (29.0%) had negative lymph nodes with no evidence of tumour. Lymph node responders had a significant survival benefit compared to patients without lymph node response, but shorter than those with negative lymph nodes (median: 27 vs 18 vs NR months, p < 0·001). On multivariable analysis, lymph node responders had an improved overall (Hazard ratio (HR): 0.86, 95% CI: 0.80–0.92, p < 0.001) and recurrence-free (HR: 0.90, 95% CI: 0.82–0.98, p = 0.030) survival. Conclusion: Lymph node regression is an important prognostic factor, warranting closer evaluation over primary tumour response to help with planning further adjuvant therapy in these patients.